2003
DOI: 10.1590/s1516-44462003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and difficulties questionnaire (SDQ): a study of school children in Ribeirão Preto

Abstract: SDQ can be useful for a preliminary screening in the investigation of possible psychiatric disorders in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
4
22

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 17 publications
(21 reference statements)
6
48
4
22
Order By: Relevance
“…The SDQ is a well-established behavioural screening tool that has been used in different cultures. This tool was found useful in both high and low-income countries in the investigation of child mental health profiles (2,6). In this study, factor analysis showed that most items loaded on the expected factors, except for the peer items, and two of the conduct items.…”
Section: General Health Statusmentioning
confidence: 64%
“…The SDQ is a well-established behavioural screening tool that has been used in different cultures. This tool was found useful in both high and low-income countries in the investigation of child mental health profiles (2,6). In this study, factor analysis showed that most items loaded on the expected factors, except for the peer items, and two of the conduct items.…”
Section: General Health Statusmentioning
confidence: 64%
“…Este resultado suscita algumas hipóteses, tais como o fato das crianças participantes do presente estudo serem provenientes exclusivamente de famílias residentes em bairros periféricos da cidade, população vinculada às escolas municipais da cidade de São Carlos. Isso não é comum nos estudos de prevalência que, em sua maioria, consideram, a população geral de crianças e adolescentes, abarcando regiões diferentes de uma mesma cidade, a partir de escolas públicas e particulares e pertencentes a populações de menor e maior renda 11,25,26 . Um estudo desenvolvido por Fleitlich e Goodman 25 em Campos do Jordão com crianças e adolescentes provenientes de três áreas distintas da cidade (uma favela, uma comunidade urbana bem estabelecida e uma comunidade rural), utilizou o SDQ para avaliar a saúde mental de crianças e adolescentes e estimou a prevalência dessa problemática por meio de análises distintas, de acordo com a situação socioeconômica dos participantes.…”
Section: Discussionunclassified
“…Another study with the SDQ in the southeastern Brazilian city of Ribeirão Preto-SP, found a rate of 12.5% of probable mental health problems in a small sample of 112 children aged 6-11 years. 3 Fleitlich-Bilyk & Goodman conducted another important epidemiological study in a population-based sample of 1,412 children aged from 7 to 14 years old in the southeastern city of Taubaté-SP, using the Development and Well-Being Assessment-DAWBA interview. 4 The authors found an overall prevalence of psychiatric disorder of 12.7%.…”
Section: Introductionmentioning
confidence: 99%